Предмет: Алгебра, автор: cgghhfrty

Помогите решить номер 60 пожалуйста!

Приложения:

Ответы

Автор ответа: snow99
1

( \frac{2a}{2a + b}  -  \frac{4 {a}^{2} }{4 {a}^{2} + 4ab +  {b}^{2}  } ) \div ( \frac{2a}{4 {a}^{2}  -  {b}^{2} }  +  \frac{1}{b - 2a} ) = ( \frac{2a}{2a +  b} -  \frac{4 {a}^{2} }{ {(2a + b)}^{2} } ) \div ( \frac{2a}{(2a - b)(2a + b)}  -  \frac{1}{2a - b} ) =  \frac{2a(2a + b) - 4 {a}^{2} }{ {(2a + b)}^{2} }  \div  \frac{2a - (2a + b)}{(2a - b)(2a + b)}  =   \frac{4 {a}^{2}  + 2ab - 4 {a}^{2} }{ {(2a + b)}^{2} }  \div  \frac{2a - 2a - b}{(2a - b)(2a + b)}  =  \frac{2ab}{ {(2a + b)}^{2} }  \div  \frac{ - b}{(2a - b)(2a + b)}  =  \frac{2ab}{ {(2a + b)}^{2} }  \times  \frac{(2a - b)(2a + b)}{ - b}  =  -  \frac{2a(2a - b)}{2a + b}
Похожие вопросы
Предмет: Математика, автор: АлёнаВайн2005